Shear bond strength of resin bonded zirconia and lithium disilicate – effect of surface treatment of ceramics and dentin - Mina Aker Sagen; Linda Vos; Jon E. Dahl; Hans J. Rønold (Biomaterial Investigations in Dentistry, 2022)
Objectives:The purpose of the study was to investigate the effect of ceramic surface pretreatment, effect of resin cement and dentin surface roughness on shear bond strength. Methodology: Zirconia rods (n = 140) were randomly assigned to air born particle abrasion with aluminum oxide (Al2O3) or hot etching with potassium hydrogen difluoride (KHF2). Lithium disilicate rods (LDS; n = 50) etched with hydrofluoric acid served as reference material. In Part 1 of the study, ceramic rods were cemented to bovine dentin using 5 dual-polymerizing resin cements (Variolink Esthetic, Multilink Automix (Ivoclar Vivadent), Duo-Link (BISCO Dental), Panavia F2.0 (Kuraray Dental), RelyX Unicem (3 M)). Shear bond strength was tested and fracture morphology determined. In Part 2 of the study, test groups with the highest frequency of adhesive fractures between cement and dentin were selected for further bond strength testing with different surface roughness of dentin; ground with P1200 or P80 silicon carbide paper. Dentin samples were fractured vertically to the cemented surface and the adherence between cement and dentin was studied. Results: The results of Part 1 showed that hot etching of zirconia significantly improved bond strength to Duo-Link cement. In Part 2, RelyX Unicem showed significantly higher bond strength to P1200 compared to P80 ground dentin. For Variolink Esthetic, bond strengths to P1200 and P80 ground dentin were similar. Adhesive fracture between cement and dentin dominated. Conclusions: A smooth dentin surface (P1200) improved bond strength to RelyX Unicem. Surface roughness was not important for Variolink Esthetic.